A vaccinia virus-vectored Hantaan virus vaccine protects hamsters from challenge with Hantaan and Seoul viruses but not Puumala virus. - Chu, Y K (1995)
To investigate the ability of a vaccinia virus-vectored vaccine expressing the M and the S segments of Hantaan (HTN) virus (C. S. Schmaljohn, S. E. Hasty, and J. M. Dalrymple, Vaccine 10:10-13, 1992) to elicit a protective immune response against other hantaviruses, we vaccinated hamsters with the recombinant vaccine and challenged them with HTN, Seoul (SEO), or Puumala (PUU) virus. Neutralizing antibodies to HTN virus were found in all vaccinated hamsters both before and after challenge. Neutralizing antibody titers to SEO virus were present at low levels or were undetectable after two immunizations with the vaccine but were positive in all vaccinated hamsters after challenge with SEO virus and were also positive in control animals that were not challenged. Neutralizing antibodies to PUU virus were observed only in hamsters previously challenged with PUU virus. To assay for virus in the blood and tissues of the hamsters, we developed a nested reverse transcriptase (RT)-PCR with cross-reactive outer primers and serotype-specific inner primers. The RT-PCR specifically detected as little as 1 PFU of virus in serum containing high-titer neutralizing antibodies and was more sensitive than immunofluorescent antibody staining for detecting virus in lung and kidney specimens of infected hamsters. By using the RT-PCR, we found that vaccinated hamsters, challenged with HTN or SEO virus, neither were viremic nor had evidence of virus in their lungs or kidneys. In contrast, vaccinated hamsters challenged with PUU virus were viremic and had PUU virus-specific nucleic acid in their organs.